Legal Protection of Private Platform in Carrying Out the Responsibility of Maintaining User Privacy Rights - Dini Mardhatillah; Abel Parvez (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This research focuses on examining the legal protection of Electronic System Operators (PSE) in order to be consistently responsible for maintaining the privacy rights of users from state intervention that is too much into the private sphere also interferes freedom of digital business activities. This study purposed to analyze the problem of the defects legal protection provided by the state against the private rights of User because application of surveillance state and provide solutions regarding the ideal legal protection. The Research methodology use normative legal research with statute approach and conceptual approach. This study concluded that there is a threatening regulation related to private PSE and can be categorized as a form of Surveillance state in digital business world. As a result, PSE feels dilemma between wanting to protect the privacy rights of users but being subject to administrative sanctions or injuring terms&references that formed by both for submit to the state.